Active fluidic control of a cylinder in a cross-flow using synthetic jet actuation - Jackson, Diarmuid (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2016)
The objective of this body of work is to establish the effectiveness of a simple synthetic jet actuator in modifying the drag forces experienced by a cylinder in a cross flow. This is achieved through the production of a virtual hydrodynamic wake structures, using a precisely controlled positioning system, high frequency strain measurements, flow visualisation (FV), high resolution whole field velocity, turbulence intensity and vorticity measurements through the use of particle image velocimetry (PIV). This is achieved using a circular cylinder in cross-flow with an embedded synthetic jet actuator (SJA) with a span-wise rectangular orifice (slot width = 0:05 cylinder diameter). Previous studies have investigated the effects of SJAs on producing a virtual hydrodynamic profile in the lee of a cylinder for a limited range of circumferential positions, and this study intends to cover a more comprehensive range of circumferential positions and determine the optimum operating conditions for drag reduction. A 20 mm diameter cylinder was placed in a cross-flow in a 400_120 mm test section of a closed loop water tunnel, with a Reynolds number in the subcritical flow regime, which corresponds to a well-conditioned low turbulence flow, with minimal turbulence intensity and wall effects in the approaching flow. A span-wise finite-span synthetic jet orifice (0.05 x 2 cylinder diameters) is embedded in the cylinder. As the near field effects of a SJA on a cross- flow is strongly influenced by velocity ratio of the free stream velocity to the orifice velocity during the expulsion stroke, the tests are carried out by maintaining a constant cross-flow velocity, while varying the velocity ratio. The circumferential location of the synthetic jet actuator can be continuously adjusted between 0 and 180 degrees, positioning the actuator upstream, inside and downstream of the separation zone, as well as facing directly up-stream and down-stream. The effects of varying velocity ratio over a series of cylinder angles on lift and drag forces was characterised using strain gauges to give force values. This allowed for the creation of a map of effect, establishing the most effects SJA conditions to produce the maximum drag modification. Flow visualisation (FV) is used on a selection of different SJA conditions, based on their ability to modify drag over either a consistent range of frequencies or to produce sudden spikes in drag modification. These are selected to identify the vortical structures responsible for modifying the wake. It was found that the SJA alters significantly the wake structures by the suppression of and / or altering the distance of roll-up of naturally forming vortices. In the case of drag increase, the formation distance is reduced, increasing wake oscillations, producing a larger pressure drag. In the case of drag reduction two primary profiles are identified; Type I supresses completely the natural formation of shedding vortices, with only a counter clock-wise vortex being formed by the SJA, that entrains high-energy fluid directly from the cross-flow, producing a highly turbulent asymmetric wake structure. Type II partially supresses the formation of naturally occurring vortices, instead producing a self-sustaining wake structure that is not reliant on the direct entrainment of fluid from the cross-flow. Particle image velocimetry measurements are carried out in the mid-plane to characterise and establish how the virtual hydrodynamic profile identified by FV interacts with the fluid streams passing over the cylinder. The virtual profiles allow for a controlled pressure recovery, capable of reducing drag by up to 20%, and substantially reducing the far-wake thickness and turbulence. This work presents an important building block in the production of a simple, robust, low-frequency fluidic control system that is capable of reducing drag and the effective length of a wake.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin